Halloween genes AhCYP307A2 and AhCYP314A1 modulate last instar larva–pupa–adult transition, ovarian development and oogenesis in Agasicles hygrophila (Coleoptera: Chrysomelidae) - Ji-su JIN; Yi-ran LIU; Zhong-shi ZHOU; Fang-hao WAN; Jian-ying GUO (Journal of Integrative Agriculture, 2023)
In insects, ecdysteroids are synthesized by genes of the Halloween family and play important roles in several key developmental events, including molting and metamorphosis. However, the roles of these genes in Agasicles hygrophila are still largely unknown. In this study, the expression patterns of the two Halloween genes AhCYP307A2 and AhCYP314A1 were determined by quantitative PCR (qPCR) at different developmental stages. Moreover, the functions of these two genes were explored using RNA interference (RNAi), and ovarian development was observed by dissecting the ovaries of A. hygrophila females. The qPCR results showed that AhCYP307A2 and AhCYP314A1 were highly expressed in last instar larvae and in adult females. In addition, AhCYP307A2 was also highly expressed in eggs and pupae but was markedly lower than in third-instar larvae and females. The RNAi results showed that the injection of dsAhCYP307A2 or dsAhCYP314A1 markedly inhibited their expression and the transcription levels of three related AhVgs. Knockdown of AhCYP307A2 or AhCYP314A1 significantly inhibited larval molting, impaired last instar larva–pupa–adult transition, delayed ovarian development, and stopped egg production (i.e., no eggs were laid). These results indicate that AhCYP307A2 and AhCYP314A1 play important regulatory roles in last instar larva–pupa–adult transition and reproduction in A. hygrophila.